2019
DOI: 10.18321/ectj796
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Acetonitrile and Chloroform Using Structures on the Base of Porous Silicon

Abstract: In this work porous silicon samples obtained by electrochemical etching were investigated. Using scanning probe microscope the morphology of porous silicon samples was studied. To determine the thickness of the porous layer and the pore diameter, micrographs were obtained using a scanning electron microscope. The dimensions of the nanocrystallites were determined from the Raman spectra. For the detection of vapors of organic compounds, planar structures were used. The results of the study confirmed the possibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 11 publications
0
4
0
1
Order By: Relevance
“…applied 10, 20, and 30 min. as etching times in order to crystalline silicon n-type (111) and (100) wafers in order to electrochemically etch PS [35][36][37][38]. It was confirmed that, while utilizing the electrochemical etching technique, the PS's depth, width, and roughness increased as the etching time rose [39][40][41][42][43][44].…”
Section: Introductionmentioning
confidence: 83%
“…applied 10, 20, and 30 min. as etching times in order to crystalline silicon n-type (111) and (100) wafers in order to electrochemically etch PS [35][36][37][38]. It was confirmed that, while utilizing the electrochemical etching technique, the PS's depth, width, and roughness increased as the etching time rose [39][40][41][42][43][44].…”
Section: Introductionmentioning
confidence: 83%
“…S.M. Manakov et al developed a structure based on por-Si for detecting of acetonitrile and chloroform (Manakov et al, 2019). In fact, por-Si can be obtained by electrochemical etching in an electrolyte with hydrofluoric (HF) acid by applying an electric current to the silicon wafer (Zhang & Braun, 2012).…”
Section: Public Interest Statementmentioning
confidence: 99%
“…Unlike metal oxides, gas sensors based on PS do have good compatibility with current electronic technologies [15]. Manakov et al [16] used PS material as a sensitive material for a capacitive gas sensor to detect some organic compounds such as acetonitrile and chloroform. However, the PS material is usually unstable; that is, the material's surface is degraded over time under the influence of various factors [17].…”
Section: Introductionmentioning
confidence: 99%